Kecemasan Sosial dan Validasi Daring pada Karakter Link dalam Mainstream (2020) - Putri Ghina Khairunnisa; Nina Farlina; Ida Rosida; Akhmad Zakky (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2026)
This research aimed to analyze how the character Link in Mainstream (2020) experienced and expressed social anxiety within the pressures of digital visibility, using Clark and Wells’ cognitive model of Social Anxiety Disorder as the primary theoretical framework and the Uses and Gratifications (U&G) theory as the supporting framework. Clark and Wells (1995) argued that social anxiety developed through processes such as distorted self-perception, fear of negative evaluation, self-focused attention, and maladaptive safety behaviors. Meanwhile, the U&G theory explained how audiences actively sought entertainment, identity reinforcement, social interaction, and validation, which in turn shaped a content creator’s behavioral patterns. This study employed a qualitative descriptive method by analyzing selected scenes, dialogue, and visual elements that illustrated Link’s psychological tension and online engagement. The findings revealed that Link’s social anxiety manifested through defensive speech, emotional withdrawal, exaggerated self-blame, and heightened sensitivity to public criticism. The analysis also showed that audience gratifications played a major role in influencing Link’s online behavior, pushing him toward extreme actions to maintain attention and approval. Overall, the research concluded that Link’s characterization reflected the destructive interaction between social anxiety and the pursuit of online validation within digital culture. These results contribute to a broader understanding of how films portray psychological vulnerability shaped by digital pressures.